Rinolitiase: Atualizacao e relato de caso - Montovani, Jair Cortez [UNESP]; Bretan, Onivaldo [UNESP]; Yamashita, Seizo [UNESP]; Marinho, N. G R [UNESP]; Yoshinaga, S. [UNESP] (My University, 1997)
Rhinoliths are rares and, in general, develop in response to foreign body lodged in the nose. This study briefly comments the clinics features of one case of rhinolithiasis that occurred during two years period. The etiology of rinoliths, differencial diagnosis and a review of the literature are also included. The authors concluded that the presence of calcified stones must be considered in cases of sinusitis or rhinitis not responding to medical therapy.
Rhinolithiasis: Update and case report
Keywords: Antrolithiasis; Rhinoliths; adult; antibiotic therapy; case report; clinical feature; computer assisted tomography; differential diagnosis; female; foreign body; human; nose disease; rhinitis; sinusitis; stone formation